Splanchnic vein thromboses associated with myeloproliferative neoplasms: An international, retrospective study on 518 cases. Issue 2 (29th November 2019) - Sant'Antonio, Emanuela; Guglielmelli, Paola; Pieri, Lisa; Primignani, Massimo; Randi, Maria Luigia; Santarossa, Claudia; Rumi, Elisa; Cervantes, Francisco; Delaini, Federica; Carobbio, Alessandra; Betti, Silvia; Rossi, Elena; et al.
Abstract: Myeloproliferative Neoplasms (MPN) course can be complicated by thrombosis involving unusual sites as the splanchnic veins (SVT). Their management is challenging, given their composite vascular risk. We performed a retrospective, cohort study in the framework of the International Working Group for MPN Research and Treatment (IWG‐MRT), and AIRC‐Gruppo Italiano Malattie Mieloproliferative (AGIMM). A total of 518 MPN‐SVT cases were collected and compared with 1628 unselected, control MPN population, matched for disease subtype. Those with MPN‐SVT were younger (median 44 years) and enriched in females compared to controls; PV (37.1%) and ET (34.4%) were the most frequent diagnoses. JAK2 V617F mutation was highly prevalent (90.2%), and 38.6% of cases had an additional hypercoagulable disorder. SVT recurrence rate was 1.6 per 100 patient‐years. Vitamin K‐antagonists (VKA) halved the incidence of recurrence (OR 0.48), unlike cytoreduction (OR 0.96), and were not associated with overall or gastrointestinal bleeding in multivariable analysis. Esophageal varices were the only independent predictor for major bleeding (OR 17.4). Among MPN‐SVT, risk of subsequent vascular events was skewed towards venous thromboses compared to controls. However, MPN‐SVT clinical course was overall benign: SVT were enriched in PMF with lower IPSS, resulting in significantly longer survival than controls; survival was not affected in PV and slightly reduced in ET. MPN‐U with SVT (n = 55) showed a particularly indolent phenotype, with no signs of disease evolution. In the to‐date largest, contemporary cohort of MPN‐SVT, VKA were confirmed effective in preventing recurrence, unlike cytoreduction, and safe; the major risk factor for bleeding was esophageal varices that therefore represent a major therapeutic target.